Encouraging Soeaking Through the Use of Storytelling - Díaz Edith; Rodríguez Claudia; Triana Lucía (Universidad Nacional de Colombia, 2000)
While students were involved in English classes throughout last year (1998), it was noticed that all of them recognised isolated vocabulary, but were not able to apply it in oral or written sentences. Some action research was carried out on how the Literature Approach and the continuous repetition of stories could increase oral production. It became clear that the students enjoyed and comprehended stories and answered questions in complete sentences.